They Came to a City Based on a Play by J.B. Priestley - Priestley, John B. (BFI, 2018)
Nine disparate Britons are transported to a mysterious city where, according to their class and disposition, they find themselves either in an earthly paradise of peace and equality or a hell starved of ambition and riches. From the pen of JB Priestley, this fantastical allegory is a striking expression of post-war utopian impulses and among Ealing's most unusual features. Presented here in a new 2K transfer from the best surviving 35mm element, this rarely seen British classic is available for home viewing for the very first time. Directed by Basil Dearden (The Captive Heart, Victim) and starring John Clements, Googie Withers and Raymond Huntley. [www.amazon.co.uk]